Vaginal Infection: Review Article - Faisal Hatem Al-Mugdadi, Suhad; Kadhim Hashem Al-Zwaini, Yasser; Mohammed Al Sayyid , Maha (University of Thi-Qar Journal of Science, 2022)
Vaginitis is a disorder characterized regarding to abnormal bad odor vaginal discharge, discomfort , itching, and burning. Bacterial vaginosis, particularly Gardnerella vaginalis, vulvovaginal candidiasis, particularly Candida albicans, and trichomoniasis are the most common causes of vaginitis. When a cause is established, bacterial vaginosis is implicated in 40% to 50% of cases, with vulvovaginal candidiasis accounting for 20% to 25% of cases and trichomoniasis accounting for 15% to 20% of cases. Physical examination , symptoms, , and laboratory testing are used for final identification. Gardnerella vaginalis DNA or vaginal fluid sialidase activity, as well as Gram stain, are now available in newer laboratory assays. A mixture of clinical manifestations, as well as potassium hydroxide microscopy, are used to diagnose vulvovaginal candidiasis. Culture and DNA probe testing are also available. For such diagnosis of trichomoniasis in asymptomatic or high-risk women, molecular approaches (nucleic acid amplification) are indicated. This study aimed to review the most recent knowledge on vaginal infection, with the most common causal agents being bacteria, yeast, and parasites Keywords—component, formatting, style, styling, insert.